1999
DOI: 10.1046/j.1365-2249.1999.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive polarization towards a T helper/cytotoxic type-1 cytokine pattern during age-dependent maturation of the immune response inversely correlates with CD30 cell expression and serum concentration

Abstract: SUMMARYIn order to investigate the T cell cytokine profile during age-dependent maturation of the immune response, we evaluated the cytokine expression of CD4 þ and CD8 þ circulating cells by flow cytometric single-cell analysis after non-specific stimulation in vitro in different age groups of normal individuals, from cord blood to adulthood. Moreover, we correlated these lymphocyte cytokine patterns with the expression/release of CD30, a member of the tumour necrosis factor (TNF) receptor superfamily, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
24
1
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 47 publications
9
24
1
2
Order By: Relevance
“…Interestingly, neonates appear to exhibit a predisposition toward production of Th2 cytokines after exposure to environmental allergens [85,2], followed by an age-dependent change toward Th-1-like responses [86,87]. This Th2 bias is usually considered to be a major underlying mechanism for the development of atopy in early life, and could again be a consequence of APC defects.…”
Section: The Immune Response In Early Childhood Yearsmentioning
confidence: 99%
“…Interestingly, neonates appear to exhibit a predisposition toward production of Th2 cytokines after exposure to environmental allergens [85,2], followed by an age-dependent change toward Th-1-like responses [86,87]. This Th2 bias is usually considered to be a major underlying mechanism for the development of atopy in early life, and could again be a consequence of APC defects.…”
Section: The Immune Response In Early Childhood Yearsmentioning
confidence: 99%
“…Therefore, the finding of a sharp age-related decline in levels of IL-2R␣ in serum in conjunction with very low, stable levels of cell surface expression of CD25 indicates that T-cell function is regulated through different mechanisms at different ages in baboons. Because of the decline of IL-2R␣ in serum, we tested all animals for an increase in levels of sCD30 in serum: sCD30 is a marker indicating the anti-inflammatory activity of Th0/Th2 lymphocytes (20) and is known to be present at higher levels in healthy centenarians (14). There was no effect of age on sCD30 levels, thus suggesting lack of a major increase in Th0/Th2 activity in older baboons.…”
Section: Fig 3 Linear Regression Analysis Showing the Relationship mentioning
confidence: 99%
“…Another study has demonstrated that the serum level of sCD30 and the circulating CD30 expression in helper T cells were significantly higher in young children than in elder children and adults. This indicates that helper T cells may induce the production of more cells subjected to Th1 in older than younger people [41]. In our study, the serum level of sCD26 was not significantly correlated with age, while the serum level of sCD30 showed a significant inverse correlation with age in patients on HD.…”
Section: Discussionmentioning
confidence: 46%